Analysis of a National Biosafety System: Regulatory Policies and Procedures in Egypt - Madkour, M.; Nawawy, A.; Traynor, Patricia L. (International Service for National Agricultural Research, 2000)
During the past decade, national biosafety systems have become increasingly important mechanisms for ensuring that the use of biotechnology products not pose unacceptable risk to human health or to the environment, nor unintended constraints to technology transfer. This Country Report presents an analysis of the present status of the biosafety system in Egypt and its impact on the commercialization of genetically modified organisms (GMOs).